Spring Freeze–Thaw Stimulates Greenhouse Gas Emissions From Agricultural Soil - Badewa, Emmanuel A.; Yeung, Chun C.; Rezanezhad, Fereidoun; Whalen, Joann K.; Oelbermann, Maren (Frontiers in Environmental Science, 2022)
In temperate cold regions, the gradual resurgence of soil microbial activity during spring freeze-thaw events is frequently associated with greenhouse gas emissions. Enhanced greenhouse gas fluxes during spring freeze-thaw are related to the mineralization of bioavailable substrates, which may be elevated when soil is amended with organic residues (e.g., biobased residues such as compost, digestate, biosolids). The objective of this study was to determine the impact of biobased residues, compared to urea fertilizer, on greenhouse gas emissions during spring freeze-thaw events. The field treatments included urea (170 kg N ha-1 y-1), composted food waste (240 kg N ha-1 y-1), hydrolyzed biosolids (215 kg N ha-1 y-1), and anaerobic digestate (231 kg N ha-1 y-1). Headspace gases were sampled from a closed static chamber in each replicate plot (n=4) and categorized with three transient spring freeze-thaw phases (waterlogged, wet, and dry). Among the treatments, nitrous oxide (N2O) flux was significant difference (p<0.05) where compost had the highest emission and digestate lowest while carbon dioxide (CO2) and methane (CH4) fluxes were not significantly difference (p>0.05). The greenhouse gas fluxes were significantly different among the freeze-thaw events (p<0.05) likely due to intense microbial activity and anaerobic conditions. The CO2 and CH4 emissions were related to N2O emission (p<0.05), and soil temperature strongly correlated with CO2 fluxes. This suggested that soil warming driven by ambient conditions as well as the type and quantity of carbon input influenced soil microbial activity, leading to greenhouse gases production. Therefore, soil amended with biobased residues may either increase or reduce greenhouse gas fluxes during spring freeze-thaw events depending on the source and production method of the organic material.